The interaction effects between summer heat exposure and economic development on the settlement intention in floating population in China - Luyang Wang; Yang Zhao; Guangcheng Wang; Jikai Xia; Yukun Shi; Hongyu Li; Wenhui Gao; Shijia Yuan; Ronghang Liu; Surong Zhao; Chunlei Han (BMC, 2024)
Abstract Limited studies examined the interaction effects between summer heat exposure and economic development on the settlement intention, especially for the floating population. Binary logistic regression model was used to examine the association of summer temperature, per capita GRDP (PGRDP), summer temperature × PGRDP with settlement intention. Additive interaction term for summer temperature and PGRDP level was used to test the interactive effects. This study indicates that summer heat exposure will decrease the settlement intention of migrants (OR:1.386, 95% CI: 1.35-1.423), while PGRDP will increase settlement intention (OR: 0.893, 95% CI: 0.870-0.917). There is a negative interaction between summer temperature and PGRDP in the additive model. To a certain extent, summer heat exposure can weaken the attractiveness of economic development for migrants to settle down, they prefer to settle in cities with favorable temperatures and high levels of economic development. Stratified analyses illustrated that summer heat exposure showed lower settlement intention among female, the elderly, engaged in agriculture and industry and living in central China. The government should take measures about mitigation, adaptation and balancing economic development and climate change to reduce the adverse impacts of summer heat, and pay more attention to vulnerable groups and backward regions.